Endoscopic Resection of Giant Colonic Lipoma: Case Series with Partial Resection - Kim, Gun Woo (The Korean Society of Gastrointestinal Endoscopy, 2013)
Colonic lipoma, a very rare form of benign tumor, is typically detected incidentally in asymptomatic patients. The size of lipoma is reported variously from 2 mm to 30 cm, with higher likelihood of symptoms as the size is bigger. Cases with symptom or bigger lesion are surgically resected in principle; endoscopic resection, which has developed recently with groundbreaking advance of endoscopic excision technology, is being used more often but with rare report of success due to high chance of complications such as bowel perforation or bleeding. The authors report here, together with a literature review, our experiences of three cases of giant colonic lipomas showing complete remission after aggressive unroofing technique, at certain intervals, using snare catheter at the origin of the lipoma so that the remaining lipoma could be drained out of the exposed surface spontaneously, in order to reduce complications.